Aquisição da leitura e escrita na educação de jovens e adultos: um estudo bibliográfico - JESUS, Kelly Cristina Mendonça de (2019)
The acquisition of reading and writing in the Education of Young and Adults (EJA) constitute simultaneous processes in the schooling of these subjects, with peculiar characteristics when compared to the process of children's literacy. In this sense, the present monograph seeks to know, from the Brazilian theorists who discuss this theme, how the process of acquiring reading and writing in the scope of youth and adult education occurs. It is a research anchored in the presuppositions of the qualitative research approach, of the bibliographic type. For the development of the study, works such as scientific articles, books, theses and dissertations were searched for, understanding the object of study, which deals with the acquisition of reading and writing in the EJA. (1990), Souza (2012), Brandão (1940), Paulo Freire (1979, 2008), Soares (2001), Silva (2009) and Almeida and Corso (2014). According to the bibliographical research carried out, by means of manual and electronic, it was possible to verify that the education of young people and adults goes beyond the act of reading and writing, since this modality of education allows the students to be critical beings, participatory before the processes in which they are being submitted. Finally, the study demonstrated that the acquisition of reading and writing is based on methods and techniques, thought according to the context, culture and reality of learners.